The Pathogen–Host Interface in Three Dimensions: Correlative FIB/SEM Applications - Weiner, Allon; Enninga, Jost (Trends in microbiology (Regular ed.), 2019)
Pathogens survive and propagate within host cells through a wide array of complex interactions. Tracking the molecular and cellular events by multidimensional fluorescence microscopy has been a widespread tool for research on intracellular pathogens. Through major advancements in 3D electron microscopy, intracellular pathogens can also be visualized in their cellular environment to an unprecedented level of detail within large volumes. Recently, multidimensional fluorescence microscopy has been correlated with volume electron microscopy, combining molecular and functional information with the overall ultrastructure of infection events. In this review, we provide a short introduction to correlative focused ion beam/scanning electron microscopy (c-FIB/SEM) tomography and illustrate its utility for intracellular pathogen research through a series of studies on Shigella, Salmonella, and Brucella cellular invasion. We conclude by discussing current limitations of and prospects for this approach. A current challenge in studying pathogen–host interactions is understanding how molecular players and cellular mechanisms function in the three-dimensional cellular environment at subdiffraction resolution. FIB/SEM is an emerging technique that can be used to investigate expansive three-dimensional cellular interfaces between pathogen and host at ultrastructural resolution. The correlation of FIB/SEM with fluorescence microscopy (c-FIB/SEM) enables the study of transient or rare infection events while also providing molecular specificity within the ultrastructural landscape. Recently, c-FIB/SEM has revealed fundamental aspects of the mechanisms of cellular invasion by Shigella, Salmonella, and Brucella. c-FIB/SEM is becoming an indispensable tool for pathogen research as it can provide a wealth of biological information not obtainable by other technologies.